PAST, PRESENT, AND FUTURE OF EMERGENCY DISPATCH RESEARCH: A SYSTEMATIC LITERATURE REVIEW. Issue 9 (18th August 2016) - Gardett, Isabel; Clawson, Jeff; Scott, Greg; Barron, Tracey; Patterson, Brett; Olola, Christopher
Abstract : Abstract previously published in Annals of Emergency Dispatch and Response.